Modified alcohol-formalin cell block: a valuable adjunct for cytodiagnosis in suspected malignant pleural effusions - Mary Thomas, Sonia; GK, Parvathidevi (Journal of Chitwan Medical College, 2025)
Introduction: Pleural fluid cytology is essential for diagnosing malignant pleural effusions and other pleural pathologies. Conventional smears (CS) are commonly used to study pleural effusions, but the modified cell block (MCB) method can enhance diagnostic accuracy. This study compares the diagnostic yield of CS alone versus combined with MCB in pleural fluid cytology. The aim of this study was to determine the comparative diagnostic value of CS techniques and a combined approach using the MCB method in the cytological analysis of pleural fluid. Method: This cross-sectional study included samples of pleural fluid over 2 years from Nov 2016 to Oct 2018. Each fluid sample was divided into two parts for evaluation using (CS+MCB techniques. Ethical approval was obtained from the institution. Clinical parameters, along with microscopic findings such as cellularity and morphological preservation on CS and MCB, were compared. Result: In 102 samples, the combined method (conventional smear+MCB) showed a significantly higher diagnostic yield for malignancy with an additional 9 cases (180%), compared to CS alone. MCB demonstrated superior cellularity and morphological preservation. Conclusion: Combining CS with MCB in our study resulted in enhanced cellularity and morphological details, leading to more accurate diagnoses. This study highlights the role of MCB in significantly improving the diagnostic accuracy of pleural fluid cytology, as compared to CS alone, especially in malignancy.